Is Bioavailable Vitamin D Better Than Total Vitamin D to Evaluate Vitamin D Status in Obese Children? - Gülin Karacan Küçükali; Özlem Gülbahar; Şervan Özalkak; Hasan Dağlı; Serdar Ceylaner; Zehra Aycan; Şenay Savaş Erdeve (Galenos Yayincilik, 2021)
Objective:Free hormones are biologically more active in target tissues. Thus, measurement of vitamin D taking into account bioavailability and free vitamin D may be preferable, especially when evidence is contradictory, as in obese children. In order to assess bioavailablity and free vitamin D, using a previously reported formula, vitamin D-binding protein (VDBP) level was measured and VDBP polymorphisms were also evaluated because of variations in binding affinity.Methods:Eighty-four obese and 78 healthy children were included. Anthropometry, calcium, phosphorus, alkaline-phosphatase, parathyroid hormone (PTH), 25 hydroxyvitamin D [25(OH)D], bioavailable-free vitamin D, and VDBP concentration and polymorphism were evaluated in the whole group.Results:Obese girls had significantly higher PTH than normal weight girls (p=0.001). Regardless of gender, obese children had significantly higher concentrations of VDBP (p=0.008) and PTH (p=0.002). When samples taken in winter were analyzed, PTH and VDBP were found to be higher and bioavailable and free vitamin D lower in the obese group. There was no difference in terms of total vitamin D between groups during the winter season.Conclusion:While total, free, and bioavailable vitamin D in the obese group was similar to the control group in autumn, free and bioavailable vitamin D in the winter was lower in the obese than the control group. In addition, PTH was higher in the obese group in both autumn and winter. Therefore, more research is needed to evaluate the variability of free and bioavailable vitamin D according to body habitus, season and the effect any differences may have.